Data set for the Commun. Chem. article by Paul et al. with the title "13C- and 15N-labeling of amyloid-β and inhibitory polypeptides to study their interaction via nanoscale infrared spectroscopy" - Paul, Suman; Jeništová, Adéla; Vosough, Faraz; Berntsson, Elina; Mörman, Cecilia; Jarvet, Jüri; Gräslund, Astrid; Wärmländer, Sebastian K. T. S.; Barth, Andreas (Stockholm University, 2023)
The data published here are the basis for the article by Paul et al. in Commun. Chem. with the title

13C- and 15N-labeling of amyloid-β and inhibitory polypeptides to study their interaction via nanoscale infrared spectroscopy

and for the Research Square preprint by Paul et al. with DOI: 10.21203/rs.3.rs-2141341/v1 (https://doi.org/10.21203/rs.3.rs-2141341/v1) and title

13C-isotope-editing of nanoscale infrared images reveals the action of an inhibitory peptide against amyloid-β aggregation.

These publications show that 13C, 15N-labeling can be used to discriminate between two peptides in nanoscale images of their infrared absorption, even when they have similar secondary structure. We studied different aggregation states of the amyloid-β peptide (Aβ) and its interaction with an inhibitory cell-penetrating peptide (NCAM1-PrP) using scattering-type scanning near-field optical microscopy (s-SNOM). Labeled and unlabeled peptides could be distinguished by comparing images of the optical phase taken at wavenumbers characteristic for either the labeled or the unlabeled peptide.

Some of the provided files require particular software to view them: Gwyddion (http://gwyddion.net/) is needed for image files, neaPLOT (attocube) for nano-FTIR spectra, and OPUS (Bruker) for FTIR spectra. Processed neaPLOT files were stored as csv files. OPUS files were converted to txt files but can also be read by Spectragryph (https://www.effemm2.de/spectragryph/about.html), which is free for private and academic use.
Keywords: Medical biochemistry - proteins and peptides (incl. medical proteomics); Analytical biochemistry; Molecular imaging (incl. electron microscopy and neutron diffraction); Biological physics; Analytical spectrometry; Biological Sciences; Biologi; Biochemistry; Biokemi; Medical Biotechnology (Focus on Cell Biology, (incl. Stem Cell Biology), Molecular Biology, Microbiology, Biochemistry or Biopharmacy); Medicinsk bioteknologi (inriktn. mot cellbiologi (inkl. stamcellsbiologi), molekylärbiologi, mikrobiologi, biokemi eller biofarmaci)